Prophylaxis vs. on‐demand treatment with BAY 81‐8973, a full‐length plasma protein‐free recombinant factor VIII product: results from a randomized trial (LEOPOLD II). (30th January 2015) - Kavakli, K.; Yang, R.; Rusen, L.; Beckmann, H.; Tseneklidou‐Stoeter, D.; Maas Enriquez, M.; Yang, Renchi; Zhao, Yongqiang; Sun, Jing; Wang, Xuefeng; Wu, Depei; Hlusi, Antonin; et al.
Summary Background BAY 81‐8973 is a new full‐length human recombinant factor VIII product manufactured with technologies to improve consistency in glycosylation and expression to optimize clinical performance. Objectives To demonstrate superiority of prophylaxis vs. on‐demand therapy with BAY 81‐8973 in patients with severe hemophilia A. Patients/Methods In this multinational, randomized, open‐label crossover study (LEOPOLD II; ClinicalTrials.gov identifier: NCT01233258), males aged 12–65 years with severe hemophilia A were randomized to twice‐weekly prophylaxis (20–30 IU kg−1), 3‐times‐weekly prophylaxis (30–40 IU kg−1), or on‐demand treatment with BAY 81‐8973. Potency labeling for BAY 81‐8973 was based on the chromogenic substrate assay or adjusted to the one‐stage assay. Primary efficacy endpoint was annualized number of all bleeds (ABR). Adverse events (AEs) and immunogenicity were also assessed. Results Eighty patients (on demand, n = 21; twice‐weekly prophylaxis, n = 28; 3‐times‐weekly prophylaxis, n = 31) were treated and analyzed. Mean ± SD ABR was significantly lower with prophylaxis (twice‐weekly, 5.7 ± 7.2; 3‐times‐weekly, 4.3 ± 6.5; combined, 4.9 ± 6.8) vs. on‐demand treatment (57.7 ± 24.6; P < 0.0001, anova). Median ABR was reduced by 97% with prophylaxis (twice‐weekly, 4.0; 3‐times‐weekly, 2.0; combined, 2.0) vs. on‐demand treatment (60.0). Median ABR was higher with twice‐weekly vs. 3‐times‐weekly prophylaxis during the first 6‐month treatment period (4.1 vs. 2.0) but was comparable in the second 6‐month period (1.1 vs. 2.0). Few patients reported treatment‐related AEs (4%); no treatment‐related serious AEs or inhibitors were reported. Conclusions Twice‐weekly or 3‐times‐weekly prophylaxis with BAY 81‐8973 reduced median ABR by 97% compared with on‐demand therapy, confirming the superiority of prophylaxis. Treatment with BAY 81‐8973 was well tolerated.